The Marketisation of Welfare-To-Work in Ireland: Governing Activation at the Street-Level - Michael McGann (Policy Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book assesses how the practice of contracting-out public employment services via competitive tendering and Payment-by-Results is transforming welfare-to-work in Ireland. It offers Ireland's introduction of a welfare-to-work market as a case study that speaks to wider international debates in social and public policy about the role of market governance in intensifying the turn towards more regulatory and conditional welfare models on the ground. It draws on unprecedented access to, and extensive survey and interview research with, frontline employment services staff, combined with in-depth interviews with policy officials, organisational managers and jobseekers participating in activation.
Keywords: 330; Benefits; Employment services; Ireland; Marketisation; Public policy; Social policy; Welfare-to-work; Workfare